Islamic Education in The Study of Islamic Psychology - Nurussakinah Daulay (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2014)
The aim of this paper is to explain Islamic education in the study of Islamic Psychology. Islamic psychology is a study approach to understanding human psychology and behavior based on the concept of monotheism, by means of integration between science and faith. Islamic psychology is a form of psychology that is based on the image of man in Islam, study the uniqueness and the patterns of human behavior as an expression of the experience of interaction with oneself, the environment, and the spiritual realm with the aim of improving the mental health and quality of religious life, and reaching happiness of life in the world and the hereafter. One effort to rebuild human civilization and refinement of the concept of human behavior that is educated and understand the concepts of education in Islam, as well as the refinement of the soul that is filled with faith it can be discussed in the study of the science of Psychology Islam which is based on the Qur'an and Hadis. In Islamic education has laid the foundations of the Qur'an concerning the objectives of Islamic education and materials that should be taught in Islamic education. The materials will be delivered using methods that should be attractive and essential issue in order to achieve the expected goals of Islamic education. Based on so tightly between tasks Islamic psychology with emphasis on the soul of this very influential in the science of Islamic education. Pure soul must be easy to accept and apply the concepts of Islamic education that is based on the Qur'an and the Sunnah of the Prophet Muhammad. On top of this pillar was built two basic concepts of Islamic education. The starting point here starts from the concept of man in Islam.